The Effect of CRM-Based Social Media Promotion and Product Quality on Brand Trust and its Impact on Repeat Purchases (Study of PT GoldFrance Pastry Customers Jabodetabek Area) - Melati Permata Sari; Setiarini Setiarini (Universitas Pancasila, 2026)
The purpose of this study is to investigate how CRM-based social media advertising and product quality affect brand trust and repeat purchase behavior among PT GoldFrance Pastry consumers in the Greater Jakarta region. A structured questionnaire was given to 100 respondents who had previously bought PT GoldFrance goods and were aware of the company's social media activity in order to gather primary data for this quantitative analysis. Multiple linear regression, the coefficient of determination (R2), hypothesis testing (t-test), and mediation analysis using the Sobel test were used to analyze the data. SPSS version 25 was used for all statistical methods. The findings show that product quality and CRM-based social media promotions have a favorable and substantial impact on brand trust. Additionally, recurring purchases are positively and significantly impacted by CRM-based social media advertising, product quality, and brand trust. The association between CRM-based social media marketing and repeat purchases, as well as between product quality and repeat sales, is significantly mediated by brand trust, according to the mediation study. These results show how crucial it is to strategically combine CRM-based social media marketing with reliable product quality in order to build brand confidence and promote long-term repeat business. In addition to offering useful insights for culinary enterprises in creating successful customer relationship strategies to increase customer loyalty, this study advances the body of literature on marketing management, especially in the areas of digital marketing and consumer behavior.